Characteristics of Mortality After Endovascular Thrombectomy in Patients with Acute Ischemic Stroke - Wang J; Liu Q; Hu F; Zheng H; Jiang X; Chen L; Zhou M; Guo J; Chen H; Guo F; Tang Y; Li J; et al. (Clinical Interventions in Aging, 2024)
Jian Wang,1,* Qian Liu,1,* Fayun Hu,1,* Hongbo Zheng,1 Xin Jiang,1 Lizhang Chen,1 Muke Zhou,1 Jian Guo,1 Hong Chen,2 Fuqiang Guo,3 Yufeng Tang,4 Jinglun Li,5 Dong Zhou,1 Li He1 1Department of Neurology, West China Hospital of Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2Department of Neurology, Deyang People’s Hospital, Deyang, Sichuan, People’s Republic of China; 3Department of Neurology, Sichuan Provincial People’s Hospital, University of Electronic Science and Technology of China, Chengdu, Sichuan, People’s Republic of China; 4Department of Neurology, Mianyang Central Hospital, University of Electronic Science and Technology of China, Mianyang, Sichuan, People’s Republic of China; 5Department of Neurology, Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Li He; Dong Zhou, Email heli2003new@126.com; zhoudong66@yahoo.dePurpose: Despite significant advancements in the treatment of acute ischemic stroke (AIS) with endovascular thrombectomy (EVT), post-EVT mortality remains a considerable concern. However, there is a lack of real-world epidemiological data delineating the characteristics of mortality for EVT, particularly in recent years following the widespread promotion of EVT treatment for stroke patients.Methods: This multicenter, retrospective study collected data from 721 AIS patients who died following EVT across 33 hospitals in Sichuan Province, China, from January 2019 to September 2022. The analysis sought to identify the primary causes of death within 30 days post-EVT and explore their related clinical features.Results: The leading causes of death were malignant cerebral edema (MCE) in 365 patients (50.6%), pneumonia in 180 patients (25%), and symptomatic intracranial hemorrhage (sICH) in 94 patients (13%). MCE was the predominant cause of death in anterior circulation strokes, while pneumonia prevailed in posterior circulation strokes. MCE was also the primary cause of death within one week post-EVT, but pneumonia became increasingly dominant over time. Large vessel occlusion and lower reperfusion success rate were significantly correlated with MCE. Advanced age increases the risk of death from pneumonia. Tandem occlusion and procedural complications tend to correlate with mortality from sICH.Conclusion: This study revealed that the principal causes of death after EVT included MCE, sICH, and pneumonia. MCE was found to be correlated with unsuccessful reperfusion. sICH was associated with procedural complications and the operators’ experience. Pneumonia was linked to post-EVT management, particularly for those who survived for one week.Keywords: acute ischemic stroke, endovascular thrombectomy, mortality, cerebral edema, intracranial hemorrhage, pneumonia